2019
DOI: 10.5267/j.msl.2019.7.035
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting IFRS adoption in listed companies: Evidence from Vietnam

Abstract: Nowadays, The International Financial Reporting Standards (IFRS) have been adopted in more than 160 countries. In fact, most ASEAN countries have adopted IFRS. The studies have noted the benefits of applying IFRS such as: Improving the quality of information on financial statements; Attract capital and enhance business cooperation opportunities, increase competitiveness, international integration in the world market; improve business performance, improve management and information quality; reflecting more reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…IASB, till now, issued 27 standards under IAS, 17 standards under IFRSs and 8 interpretations under International Financial Reporting Interpretation Alnaas & Rashid, 2019;Alsaeed, 2006;Appiah et al, 2016;Bunea-Bontaş, 2017;Devalle et al, 2016;Glaum et al, 2013;Samaha & Khlif, 2016). Analysing the research on compliance revealed that some studies concentrated on measuring the compliance level with all IFRSs and its association with company attributes (Kumar & Saini, 2016;Tran et al, 2019;Tsalavoutas et al, 2020). Another group of studies engaged on the level of compliance with one accounting topic such as Goodwill and goodwill impairment testing, related party transactions and income tax (Devalle et al, 2016;Lazar & Velte, 2018) The last group of studies focused on the level of compliance with one of IFRS such as IFRS 3, IFRS 7, IFRS 9 and IFRS 15 (Glaum et al, 2013;Sarea & Abdulla, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…IASB, till now, issued 27 standards under IAS, 17 standards under IFRSs and 8 interpretations under International Financial Reporting Interpretation Alnaas & Rashid, 2019;Alsaeed, 2006;Appiah et al, 2016;Bunea-Bontaş, 2017;Devalle et al, 2016;Glaum et al, 2013;Samaha & Khlif, 2016). Analysing the research on compliance revealed that some studies concentrated on measuring the compliance level with all IFRSs and its association with company attributes (Kumar & Saini, 2016;Tran et al, 2019;Tsalavoutas et al, 2020). Another group of studies engaged on the level of compliance with one accounting topic such as Goodwill and goodwill impairment testing, related party transactions and income tax (Devalle et al, 2016;Lazar & Velte, 2018) The last group of studies focused on the level of compliance with one of IFRS such as IFRS 3, IFRS 7, IFRS 9 and IFRS 15 (Glaum et al, 2013;Sarea & Abdulla, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Trinh (2019) believes that when the Ministry of Finance promulgates regulations on the application of IFRS, it will be a legal basis for training institutions to transform training programs of accounting and auditing for complying with the regulations; accordingly, lecturers must foster and update their knowledge of IFRS to meet teaching requirements, thereby contributing to improving the quality of accounting and auditing teaching staff. Similarly, there are studies by Tran et al (2019), Pham (2019).…”
Section: Regulations Of Ministry Of Finance On the Application Of Ifr...mentioning
confidence: 89%
“…Mobile Information Systems foundation for the development of management accounting informatization [13]. e research of Yousefi and Pishvaee shows that the introduction of cloud computing into management accounting information system can make reasonable use of spare resources in enterprises, and by improving the interactive use efficiency of each port of the system, it can well reduce the running cost of the system and strengthen the collaboration within enterprises [14].…”
Section: Related Workmentioning
confidence: 99%